Factors that affect job satisfaction: perceptions of child protection social workers employed by the Department of Social Development in the Johannesburg Metro Region - Tlakula, Caroline (University of the Witwatersrand, Johannesburg, 2024)
The White Paper of Social Welfare (1997) informed the restructuring of services and social welfare programmes in both the public and the private sectors to address the previously discriminating welfare services in existence during the apartheid era. Currently, one of the five main programmes rendered by the Department of Social Development (DSD) is directed at children and families. In this regard, child protection social workers play an essential role. However, before conducting the study I had personally observed that some of my work colleagues rendering child protection services did not seem to be enjoying job satisfaction. It is well known that for employees to render quality services they need to enjoy job satisfaction. Thus, the purpose of my research was to explore the perceptions of child protection social workers regarding what factors are affecting their job satisfaction. Hertzberg’s motivation- hygiene theory underpinned the research. Based on the constructivist paradigm and qualitative approach, a case study design was implemented to achieve the main aim and objectives of the study. Ten child protection social workers who are rendering services in the Johannesburg Metropolitan region were purposively recruited and selected. Data gathering took place by conducting personal, semi-structured interviews with the participants using an interview guide to steer the interviews. Thematic analysis was employed to analyse the data gathered. Research findings indicated specific intrinsic factors and extrinsic factors affect child protection social workers’ job satisfaction. These findings will be made available to the management of the DSD in the Johannesburg Metro Region.
A research report Submitted in fulfillment of the requirements for a MA degree in Occupational Social Work, In the Faculty of Humanities , School of Human and Community development, University of the Witwatersrand, Johannesburg, 2024
Keywords: 1.1 job satisfaction; occupational social worker; Department of Social Development; child protection social worker; UCTD; SDG-8: Decent work and economic growth